Modelling and Analysis of Covid-19 Spread Among People in a Queue - Mathews, Santhosh Samuel (International Journal of Scientific Research in Biological Sciences, 2020)
Covid-19 is a serious respiratory disease that quickly spread around the world. It is essential to understand how coronavirus transmits from one person to another and this knowledge will help to limit the spread of the Coronavirus. A computer simulation is used to understand the possibilities of spreading of Coronaviruses among people standing in the queue. The model parameter that represents the height of the person is fed with 1.51 meters to 1.75 meters and inhaled virus count is determined. Repeated the study to find the effect of the transmission of coronavirus on positions 1 to 5 from the infected person in the queue. In another experiment, the waiting time in the queue is varied from 30 seconds to 150 seconds. Also, the distance between people in the queue is varied from 0.5 meters to 3 meters and determined the risk of getting infected. The relative height of the person with reference to the patient is one of the key factors that determine the risk of infection. Also observed that the people are more susceptible to Covid-19 when they are just behind the infected person and spend more time in the queue. The increased distance between people in the queue has not reduced the probability of spreading of coronavirus at least up to 3 meters. In summary, this study suggests that in addition to social distancing and personal hygiene, wearing face masks will further reduce the probability of spreading of Covid-19 in social gatherings.